The Quechua alphabet and the First Congress of Academies - Villasante Ortiz, Segundo (1987)
One of the main issues and concerns of the First National and International Congress of Quechua and Aymara Academies, held in the city of Cusco in February of this year, has been the final approval of the Quechua and Aymara alphabet, whose approaches and The discussions were in charge of Commission 01, which was unable to focus or specify because the majority opinion of the attending delegations was not within the personal criteria of the directors of the aforementioned Work Commission, motivating its abandonment. Situation that forced the Directory of the Congress to assume the conclusion of the discussion and approval of the use of three vowels (a, i, u) or five vowels (a, e, i o, u) for the Quechua alphabet, whose final result was the following: 25 delegations for the use of the five members, one delegation for three members and one abstention, thus concluding the two-day discussion, promoted by the Commission.